Changing Emergency Department and hospital organization in response to a changing epidemic - Ivo Casagranda; Daniele Coen; Ciro Paolillo; Mario Cavazza; Gianfranco Carvellin; Andrea Bellone; Stefano Perlini (Emergency Care Journal, 2020)
The world is facing a new pandemic that sets the national health systems, their structures and professionals in a crisis never experienced before. (...)